POLITIK HUKUM PEMBENTUKAN PERATURAN DAERAH PROVINSI NOMOR 7 TAHUN 2019 TENTANG PERUBAHAN ATAS PERATURAN DAERAH NOMOR 4 TAHUN 2016 TENTANG PEMBENTUKAN DAN SUSUNAN PERANGKAT DAERAH PROVINSI RIAU - Alfin Julian Nanda; Mexsasai Indra; Maria Maya Lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
This study aims to find out how the legal political configuration of the Formation of Provincial Regulation No. 7 2019 concerning Amendments to Regional Regulation No. 4 2016 concerning the Formation and Composition of Regional Apparatus of Riau Province. The formulation of the problem posed is what is the political configuration and legal character in the Provincial Regulation No. 7 2019 concerning the Formation and Composition of the Regional Apparatus of Riau Province from the aspect of legal politics. This research belongs to the typology of empirical juridical legal research. Research data was collected by means of document / library study and interviews with the Head of the Legal Bureau and Members of the Special Committee for Regional Regulation No. 7 2019 concerning the Formation and Composition of Regional Apparatus of Riau Province. The analysis was conducted using a statutory approach combined with related party interviews. The results of this study show the configuration of political parties that occurred in the discussion of Provincial Regulation No. 7 2019 concerning the Formation and Composition of Regional Apparatus of Riau Province, namely that there are slight differences in general views between political party factions. The organizational arrangement of regional apparatus is a common thing in an organizational cycle, including in regional government organizations. The process of its birth until the discussion of Regional Regulation No. 7 2019 concerning the Formation and Composition of Regional Apparatus of Riau Province by the DPRD Riau Province is one example of a legal product that is reflects the fulfillment of the demands of individuals and social groups in society so that it is better able to reflect a sense of justice in society. The suggestion put forward by the author is that there is a need for good coordination between the Regional Secretariat Organization Division with all OPD and DPRD as well as all state civil servants who are in the scope of Riau Province. In the process of implementing this regional apparatus regulation, additional facilities and infrastructure should be made as well as provisioning needed by the state civil apparatus in realizing regional apparatus institutions in accordance with the applicable Regional Regulations.